An introduction to the WHO 5th edition 2022 classification of testicular tumours. Issue 4 (1st July 2022) - Berney, Daniel M; Cree, Ian; Rao, Vishal; Moch, Holger; Srigley, John R; Tsuzuki, Toyonori; Amin, Mahul B; Comperat, Eva M; Hartmann, Arndt; Menon, Santosh; Netto, George J; Rubin, Mark A; et al.
Abstract : The 5th edition of the World Health Organisation Blue Book was published recently and includes a comprehensive update on testicular tumours. This builds upon the work of the 4th edition, retaining its structure and main nomenclature, including the use of the term 'germ cell neoplasia in situ' (GCNIS) for the pre‐invasive lesion of most germ cell tumours and division from those not derived from GCNIS. While there have been important developments in understanding the molecular underpinnings of testicular cancer, this updated classification paradigm and approach remains rooted in morphology. Nomenclature changes include replacement of the term 'primitive neuroectodermal tumour' by 'embryonic neuroectodermal tumour' based on the non‐specificity of the former term and to separate these tumours clearly from Ewing sarcoma. Seminoma is placed in a germinoma family of tumours emphasising relation to those tumours at other sites. Criteria for the diagnosis of 'teratoma with somatic transformation' have been modified to not include variable field size assessments. The word 'carcinoid' has been changed to 'neuroendocrine tumour', with most examples in the testis now classified as 'prepubertal type testicular neuroendocrine tumour'. For sex cord‐stromal tumours, the use of mitotic counts per high‐power field has been changed to per mm2 for malignancy assessments, and the new entities, 'signet ring stromal tumour' and 'myoid gonadal stromal tumour', are defined. Well‐differentiated papillary mesothelial tumour has now been defined as tumour type with a favourable prognosis. Sertoliform cystadenoma has been removed as an entity from testicular adnexal tumours and placed with Sertoli cell tumours. Abstract : The WHO 2022 classification changes include new nomenclature such as embryonic neuroectodermal tumour. There are new entities such as pre‐pubertal type testicular neuroendocrine tumour, signet ring stromal tumour and myoid gonadal stromal tumour. Evaluation of tumours by mitotic counts per mm 2 is now mandated.